Possible role of CD22, CD79b and CD20 expression in distinguishing small lymphocytic lymphoma from chronic lymphocytic leukemia - Jovanovic, Danijela; Djurdjevic, Predrag; Andjelkovic, Nebojsa; Zivic, Ljubica (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Flow cytometry has an important role in diagnosis and classification of B-cell lymphoproliferative disorders (BCLPDs). However, in distinguishing chronic lymphocytic leukemia (CLL) from small lymphocytic lymphoma (SLL) only clinical criteria are available so far. Aim of the study was to determine differences in the expression of common B cell markers (CD22, CD79b and CD20) on the malignant lymphocytes in the peripheral blood samples of CLL and SLL patients. Material and methods : Peripheral blood samples of 56 CLL and 11 SLL patients were analyzed by 5-color flow cytometry on the CD45/CD19/CD5 gate for CD22, CD79b and CD20. Results: In the samples collected from the CLL patients, CD22 expression was detected in only 20% of patients in the low pattern, while in SLL patients the expression was medium and present in 90.9% of patients (p < 0.0001). For CD79b expression, statistical significance is reached both in the expression pattern, which was low/medium for CLL and high for SLL, and expression level (p = 0.006). The expression of CD20 was counted as the CD20/CD19 ratio. The average ratio was 0.512 in the CLL patients vs. 0.931 in the SLL patients (p = 0.0001). Conclusions: The pattern of expression and expression level of CD22, CD79b and CD20 in peripheral blood could be used for distinguishing SLL from CLL patients.